Global health: Integrating national laboratory health systems and services in resource-limited settings - Linda M. Parsons; Akos Somoskovi; Evan Lee; Chinnambedu N. Paramasivan; Miriam Schneidman; Deborah Birx; Giorgio Roscigno; John N. Nkengasong (African Journal of Laboratory Medicine, 2012)
Laboratory systems worldwide are challenged not only by the need to compete for scarce resources with other sections of national health care programmes, but also with the lack of understanding of the critical role that laboratories play in the accurate diagnosis and monitoring of patients suffering from high-burdens of disease. An effective approach to establishing cost-effective laboratory systems that provide rapid and accurate test results for optimal impact on patient care is to move away from disease-specific programmes and establish integrated laboratory services. An integrated laboratory network provides all primary diagnostic services needed for care and treatment without requiring patients to go to different laboratory facilities for specific tests. Such a network focuses on providing quality-assured basic laboratory testing through the use of common specimen collection, reporting and diagnostic platforms that can be used across diseases. An integrated laboratory system also provides specimen transport to specialised laboratories and an environment conducive to the introduction and use of new and more complex technologies that would benefit the patient population and public health systems as a whole. As such, this article described various strategies for, and practical examples of, the successful integration of laboratory services.